APLIKASI SISTEM INFORMASI GEOGRAFIS UNTUK MEMETAKAN DISTRIBUSI SASARAN PEMANTAUAN KESEHATAN IBU DI WILAYAH KERJA PUSKESMAS I DENPASAR SELATAN - Ni Made Dian Kurniasari; Putu Ayu swandewi astuti; Tangking Widarsa; Hari Mulyawan (Program Studi Sarjana Kesehatan Masyarakat Universitas Udayana Berasosiasi Dengan Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI), 2012)
Indonesian Maternal Mortality Rate (MMR) in 2007 was 228 per 100.000 live births. A program toreduce MMR was Local Area Monitoring of Maternal Health and was conducted by Public HealthCenters (PHCs) throughout Indonesia. This study aims to apply geographic information system(GIS) as a tool to provide maps which describe the target of local area monitoring of maternalhealth, the distribution of maternity health centers, and level of poverty in the catchment area ofSouth Denpasar I PHC in November to December 2010.This study used descriptive research with a cross sectional approach. Samples were pregnant women, mothers that had giving birth and maternity health centers in the catchment area ofSouth Denpasar I PHC from November to December 2010.The results showed GIS can be used to create maps to describe various data of maternal healththat relates to Local Area Monitoring. The type of maps that were generated for this study werechoropleth maps, dot density maps, point location maps, a combination of choropleth maps withpoint location maps and bu? ering maternity health center maps.The recommendation is that PHCs should consider using GIS as a tool for presenting data relatedto local area monitoring of maternal health. More advanced uses of GIS as a tool to analyze dataand to visualize the results of other research which is related to maternal health and geographicconditions is worth exploring.